APPLYING DEMATEL TO DISCUSS KEY FACTORS IN SHAPING ORGANISATIONAL CULTURE OF LEAN MANAGEMENT - Lu, Mei-Ling; Fan, Ping-Hsin (The South African Journal of Industrial Engineering, 2023)
This study aimed to discuss the factors in shaping organisational culture when an organisation promotes lean management. It also aimed to explore which factors are critical among these factors. This study applied a survey questionnaire methodology, and obtained the consent of ten experts and scholars through purposive sampling. The survey was implemented by respondents completing the questionnaires themselves or through telephone interviews. The data were analysed by applying a decision-making trial and evaluation laboratory to understand the degree of causality and correlation between the criteria. According to the data analysis results, three dimensions – ‘Lean management has substantial benefits‘, ‘Prevent process waste‘, and ‘Implement lean management programmes and activities/methods and tools’ – had the highest degree of correlation; and three dimensions – ‘Lean management has substantial benefits‘, ‘Base your management decisions on a long-term philosophy‘, and ‘Prevent process waste’ – had the highest degree of causality. Together these dimensions formed the group of causes. However, the degree of causality of ‘Lean management has substantial benefits’ was far greater than that of the other dimensions. This indicated its significance and influence. The degree of causality of ‘Implement lean management programmes and activities/methods’ was far less than that of the other dimensions, indicating that this dimension was the effect and was influenced by the other five dimensions. Overall, ‘Lean management has substantial benefits’ was the most critical factor with the highest degree of causality and correlation. Regarding management implications, a business organisation must encourage its members to regard this dimension as the most critical element when it promotes and shapes the organisational culture of lean management.